eDNA-Based Early Detection Illustrates Rapid Spread of the Non-Native Golden Mussel Introduced into Beijing via Water Diversion - Wei Guo; Shiguo Li; Aibin Zhan (Animals, 2024)
The world’s largest water diversion, the South-to-North Water Transfer Project (SNWTP) in China, has created an “invasion highway” to introduce invasive golden mussels (Limnoperna fortunei) from the Yangtze River basin to Beijing. To examine the spread and colonization patterns of this newly introduced invasive species, we conducted comprehensive environmental DNA (eDNA)-based early detection and conventional field surveys across all water bodies in five river basins in Beijing from 2020 to 2023. Our results indicated a rapid spread over the past four years. Among the 130 tested sites, the number of sites with positive signals from eDNA analysis exhibited an annual increase: Commencing with four infested sites identified through field surveys in 2019, eDNA analysis detected an additional 13, 11, and 10 positive sites in 2020, 2021, and 2022, respectively, and a substantial rise comprising an additional 28 sites in 2023. Conventional field surveys detected mussels 1–3 years later than eDNA-based analysis at 16 sites. Across all 16 sites, we detected a low population density ranging from 1 to 30 individuals/m2. These findings collectively indicate that the invasions by golden mussels in Beijing are still in their early stages. To date, golden mussels have successfully colonized four out of the five investigated river basins, including the Jiyun River (22.2% positive sites), North Canal River (59.6% positive sites), Chaobai River (40% positive sites), and Yongding River (63.6% positive sites), with the North Canal River and Yongding River being the most heavily infested. Currently, only the Daqing River basin remains uninfested. Given the significant number of infested sites and the ongoing transport of large new propagules via SNWTP, further rapid spread and colonization are anticipated across aquatic ecosystems in Beijing and beyond. Consequently, we call for the proper implementation of effective management strategies, encompassing early detection, risk assessment, and the use of appropriate control measures to mitigate the potential ecological and economic damages in invaded ecosystems.